Ab initio phasing of the diffraction of crystals with translational disorder. Issue 1 (20th December 2018) - Morgan, Andrew J.; Ayyer, Kartik; Barty, Anton; Chen, Joe P. J.; Ekeberg, Tomas; Oberthuer, Dominik; White, Thomas A.; Yefanov, Oleksandr; Chapman, Henry N.
Abstract : This article reports on the combined use of Bragg reflections and diffuse scatter for structure determination in crystallography. Abstract : To date X‐ray protein crystallography is the most successful technique available for the determination of high‐resolution 3D structures of biological molecules and their complexes. In X‐ray protein crystallography the structure of a protein is refined against the set of observed Bragg reflections from a protein crystal. The resolution of the refined protein structure is limited by the highest angle at which Bragg reflections can be observed. In addition, the Bragg reflections alone are typically insufficient (by a factor of two) to determine the structure ab initio, and so prior information is required. Crystals formed from an imperfect packing of the protein molecules may also exhibit continuous diffraction between and beyond these Bragg reflections. When this is due to random displacements of the molecules from each crystal lattice site, the continuous diffraction provides the necessary information to determine the protein structure without prior knowledge, to a resolution that is not limited by the angular extent of the observed Bragg reflections but instead by that of the diffraction as a whole. This article presents an iterative projection algorithm that simultaneously uses the continuous diffraction as well as the Bragg reflections for the determination of protein structures. The viability of this method is demonstrated on simulated crystal diffraction.